Progress of Selected Products 1957 Part I - Summary - Planning Commission (Planning Commission Government of India, 1957)
The Progress of Selected Projects up to 31st March 1957 report provides a detailed assessment of key development initiatives under India’s Second Five Year Plan, focusing on strategic sectors such as steel, railways, irrigation, and power. Forty major projects, including 37 public sector and 3 private sector initiatives, received a total investment of Rs. 3,113.8 crores, representing 21% of the plan’s total outlay. The steel sector, highlighted as a national priority, saw production expansion through the Bhilai, Rourkela, and Durgapur plants, with significant output targets set to meet rising industrial demands. Railway improvements included record production at Chittaranjan Locomotive Works, while fertilizer production capacity, led by the Sindri Fertilizer Factory, aimed to support agricultural growth. Multi-purpose irrigation and power projects, such as the Bhakra-Nangal and Damodar Valley initiatives, targeted extensive irrigation coverage and increased electricity generation. While the report notes notable achievements by March 1957, it also highlights challenges in completing projects on schedule and ensuring inter-agency coordination. The framework of ongoing monitoring underscores the government’s commitment to strategic sectoral development, providing a foundation for performance accountability and continued progress toward the objectives of the Second Five Year Plan.
Statistics and Surveys Division May, 1957
Statistics and Surveys Division May, 1957
Keywords: Second Five Year Plan; Steel Production; Railways; Irrigation Projects; Power Generation; Bhilai Steel Plant; Rourkela Steel Plant; Durgapur Steel Plant; Fertilizer Production; Damodar Valley Corporation; Bhakra-Nangal Project; Infrastructure Development